A study of organization culture and employee performance of TM Enterprise / Nur Anisa Azrin Baharudin - Baharudin, Nur Anisa Azrin (Faculty of Business and Management, 2017)
This study is to investigate the relationship between organization culture and employee performance. Three objectives have been determined in order to achieve the purpose of this study. First is to identify the relationship between competitive culture and employee performance. Second objective is to identify the relationship between entrepreneur culture and employee performance, and the last objective is to identify the relationship between bureaucratic culture and employee performance. The population of this study consists of 300 employees from department of TM Enterprise, while the sample consists of 175 respondents. The data were collected by distribute 175 questionnaires and 175 returned questionnaires were used in the study. The questionnaires designed based on three independent variables that are expected to affect employee performance which are competitive culture, entrepreneur culture and bureaucratic culture. To analyses the data, descriptive, correlation, and regression analyses was used. Hence, the results from this study reveal that there is a positive relationship between all independent variables which are competitive culture, entrepreneur culture and bureaucratic culture towards employee performance. In addition, there are many others factors that may influence employee performance which are not included in this research intend to suggests to include others factors as discuss in chapter 5. The sample of this study only limited to the employee that are working in department of TM Enterprise.